2020
DOI: 10.20473/tijab.v4.i1.2020.52-62
|View full text |Cite
|
Sign up to set email alerts
|

Tax Aggressiveness: A Meta Analysis in Agency Theory Perspective

Abstract: This study examines the phenomenon of corporate tax aggressiveness in Indonesia. The meta-analysis technique is used to find conclusions about the trends of similar research that have been studied. The sample of this study is 22 published articles for quantitative and qualitative analysis. The results of the meta-analysis show that corporate governance (independent commissioners, audit committees, and audit quality) and company characteristics (leverage, firm size, and profitability) influence tax aggressivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
1
2
0
5
Order By: Relevance
“…This research is corroborated by (Yuliana & Wahyudi, 2018) and research (Hidayat Eta Febrina, 2018). The results of this study are different from (Alkausar et al, 2020), which concluded that leverage, firm size, and profitability do not effect on tax aggressiveness.…”
Section: Debt To Asset Ratio Affects Tax Aggressivenesssupporting
confidence: 72%
“…This research is corroborated by (Yuliana & Wahyudi, 2018) and research (Hidayat Eta Febrina, 2018). The results of this study are different from (Alkausar et al, 2020), which concluded that leverage, firm size, and profitability do not effect on tax aggressiveness.…”
Section: Debt To Asset Ratio Affects Tax Aggressivenesssupporting
confidence: 72%
“…Menurut Mumtahanah & Septiani (2017) agresivitas pajak adalah suatu kondisi yang menunjukkan bahwa entitas mengambil langkah-langkah untuk mengurangi atau melebihi jumlah pajak yang terutang serta dilakukan oleh perusahaan hanya semata-mata untuk keuntungan finansial manajemen. Alkausar et. al.…”
unclassified
“…Berdasarkan Agency Theory, wajib pajak merupakan agent yang memiliki tanggung jawab kepada fiskus selaku principal untuk melaksanakan kewajiban perpajakannya (Alkausar et al, 2020). Namun, terdapat konflik kepentingan antara wajib pajak badan dengan fiskus.…”
Section: Pendahuluanunclassified